2005
DOI: 10.1634/stemcells.2005-0046
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Chemically Burned Rat Corneal Surface by Bone Marrow–Derived Human Mesenchymal Stem Cells

Abstract: To examine whether transplantation of human mesenchymal stem cells (MSCs) could reconstruct the corneal damage and also whether grafted MSCs could differentiate into corneal epithelial cells, we isolated MSCs from healthy donors. After growth and expansion on amniotic membrane, cells were transplanted into rat corneas 7 days after chemical burns. Reconstruction of the damaged cornea and the rat vision were measured once a week by slit lamp and by an optokinetic head-tracking instrument, respectively. Corneas w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
267
1
23

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 318 publications
(314 citation statements)
references
References 28 publications
23
267
1
23
Order By: Relevance
“…We chose to administer the MSCs before transplantation (day À7) as previous studies have shown enhanced efficacy when applied pretransplantation in preclinical models of cardiac (34) and kidney (35) transplantation. To date, a number of groups have investigated the ability of MSCs to repair chemically damaged corneas (20,(36)(37)(38) but relatively few have reported on the effects of MSCs on corneal allograft survival (22,39). To our knowledge, we show here for the first time that MSCs derived from a thirdparty strain are effective in prolonging corneal allograft survival.…”
Section: Discussionmentioning
confidence: 71%
“…We chose to administer the MSCs before transplantation (day À7) as previous studies have shown enhanced efficacy when applied pretransplantation in preclinical models of cardiac (34) and kidney (35) transplantation. To date, a number of groups have investigated the ability of MSCs to repair chemically damaged corneas (20,(36)(37)(38) but relatively few have reported on the effects of MSCs on corneal allograft survival (22,39). To our knowledge, we show here for the first time that MSCs derived from a thirdparty strain are effective in prolonging corneal allograft survival.…”
Section: Discussionmentioning
confidence: 71%
“…The evident, although limited growth supporting ability of human amniotic membrane may be owed to its growth factors and basement membrane components, many of which, including NGF, KGF, HGF, bFGF, TGFb, and integrins b1 and b4 have been shown to be present in the limbal epithelium and stroma as well [reviewed in (123)]. Moreover, AM also has anti-inflammatory and antiangiogenic effects (132). Recently, amniotic membrane was shown to induce overexpression of the IL-1 cytokine receptor antagonist (IL-1RA) in LESCs, and its anti-apoptotic effect was also demonstrated (133).…”
Section: Culturing Of Lescmentioning
confidence: 99%
“…The apparent flexibility of the different types of corneal stem cells may make them a useful therapeutic tool in the treatment of degenerative diseases of neural derived tissues of the eye, as well as of other organs such as the brain, and perhaps even of the heart or the pancreatic islets (141). On the other hand, stem cells from other organs may serve as autologous sources of replacement in ocular surface diseases, as has been shown in the case of bone marrow mesenchymal cells, adult epidermal or oral mucosal stem cells (126,132,157).…”
Section: Perspectivesmentioning
confidence: 99%
“…31 Similarly, human amniotic membranes have been extensively applied as substrates for corneal epithelial-derived in vitro expansion and for reconstruction of damaged cornea in several animal models (e.g., rat, rabbit, and goat). [32][33][34][35][36] However, the high inter-and intra-tissue variability in morphological, chemical, and optical properties limit the use of the human amniotic membrane in clinical settings. [37][38][39] Alternatively, human donor corneal stromal tissues have been proposed as substrates for human corneal epithelium growth, displaying, in vitro, features similar to the native limbal epithelium.…”
Section: Corneal Epitheliummentioning
confidence: 99%
“…Furthermore, several studies report methods to isolate and utilize limbal stem cells for regenerating corneal epithelium, stromal stem cells, and mesenchymal stem cells for corneal repair. 32,34,[88][89][90] Human stromal stem cells have been used to repopulate mouse corneas and restore stromal thickness, fibril deficits, and transparency in cloudy corneas found in lumican -/ -mice, 91 and in natural and synthetic polymers-based in vitro systems. 58,67 The cells were found to be stably integrated into the mouse cornea for > 10 weeks.…”
Section: Cell Sourcesmentioning
confidence: 99%